Meningkatkan Profitabilitas Bank Umum Syariah di Indonesia Melalui Islamicity Performance Index dan Operating Eficiency Ratio - Ibrahim Ibrahim; Asbi Amin; Rostiaty Yunus; Hasyim Mochtar (Al-Buhuts, 2022)
This study aims to examine the effect of Islamicity Performance Index and Operating Efficiency Ratio on Profitability at Islamic Commercial Banks in Indonesia. This research is a quantitative study, used with the ultimate goal of arriving at a resolution of the proposed theory by dissecting quantitative information. The population of this study is all Islamic Commercial Banks (BUS) registered with the Financial Services Authority (OJK) in 2016-2020, namely 14 BUS as the population in this study. Then, purposive sampling is used with the following criteria: 1) Sharia banking financial statements published successively during the period 2016, 2017, 2018, 2019, 2020 and 2021; 2) Financial statements that do not suffer losses; 3) Presenting the data needed in this study. So that the number of samples is determined to be 36 data from 6 Islamic Commercial Banks. The econometric model used is a panel data regression analysis model using the Eviews 12 application. The results found that Profit Sharing Ratio (PSR) and Operating Efficiency Ratio (OER) had a significant negative effect on Return On Assets (ROA). Meanwhile, Islamic Income Ratio (IsIR) and Zakat Performance Ratio (ZPR) did not have a significant effect on Return On Assets (ROA).